Resetting of osmoreceptor response as cause of hyponatraemia in acute idiopathic polyneuritis. Issue 6203 (8th December 1979) - Penney, M D; Murphy, D; Walters, G
Abstract : In a patient with hyponatraemia associated with acute idiopathic polyneuritis plasma concentrations of antidiuretic hormone increased when hypertonic saline was infused intravenously, and urine osmolality rose concomitantly. A water load was excreted normally, while the plasma remained extremely hypo-osmolal. It is concluded that osmoregulation was functioning normally but was set abnormally low, possibly owing to a disturbance of the peripheral volume receptors.